Drying effect on the properties of traditionally processed sago starch - Mustafa Kamal, M.; Baini, R.; Lim, S.F.; Rahman, M.R.; Mohamaddan, S.; Hussain, H. (2019)
Local people in Sarawak, Malaysia produce sago starch, commonly referred as lemantak, using traditional method for authentic meals and delicacies. The quality of lemantak degrades with time due to its high moisture content limiting the potential for a wider market, and hence affecting the socio-economy of those whose livelihood depends on sago starch production. The objective of the present work was to evaluate the changes in the properties of traditionally processed dried Sarawak sago starch. In order to achieve this, sago starch was extracted using a well-established traditional process and was dried at 40°C to produce sago starch with moisture contents of 40%, 30%, 20% and 10% wet basis. The effect of moisture content on the physical properties was studied through colour analysis, microscopic analysis, and particle size distribution. Analysis on resistant starch content was also performed. Changes on the hydration and functional properties was monitored by measuring the water absorption index (WAI), water solubility index (WSI), swelling capacity (SC), and gelatinisation behaviour. Lastly, Fourier transform-infrared spectroscopy (FT-IR) was applied to observe the changes in amorphous and crystalline areas. The physical properties analysis showed changes in starch colour and granule surface; but the change on granule size varied. Dried starch with lower moisture content exhibited higher resistant starch, absorption index, and peak temperature, but lower solubility index, swelling capacity, peak viscosity, crystalline index, and amorphous index. It is suggested that moisture content affected the changes in traditionally processed sago starch properties which was influenced by few components namely polyphenol, lipid, amylose-lipid complex, and inter-molecular hydrogen bond